Modernisasi Fungsi Security Bagi Peserta Pendidikan Dasar Satpam PT. Javas Anugerah Perkasa - Evi Lorita; Bando Amin C. Kader; Lena Elfianty; Tri Dina Ariyanti; Antonio Imanda; Cinthya Jennifer R. N (Universitas Dehasen Bengkulu, 2023)
This Community Service (PKM) aims to provide knowledge and insight to security guards who are carrying out Diksar (basic education) about public services, the rule of law, information technology, and the use of the Indonesian language that is good and right. The benefits of PKM activities are aimed at security guards (security) so that they can provide an understanding of public services, as law enforcers and comply with applicable laws or regulations, understand currently developing information technology and be able to use good and correct Indonesian according to situations and conditions . The results and conclusions of this PKM are that this PKM activity has educated and provided in-depth knowledge about the important role in terms of service and knowledge of security guards as law enforcers and obedient to rules, security guards can understand and apply information technology that is currently developing, and provide an understanding of the proper use of the Indonesian language according to the situation and conditions.